Canakinumab After Electrical Cardioversion in Patients With Persistent Atrial Fibrillation: A Pilot Randomized Trial. (July 2020) - Krisai, Philipp; Blum, Steffen; Schnabel, Renate B.; Sticherling, Christian; Kühne, Michael; von Felten, Stefanie; Ammann, Peter; Pruvot, Etienne; Albert, Christine M.; Conen, David
Abstract : Supplemental Digital Content is available in the text.